Dialektika Politik dan Agama Kerajaan Bima Tahun 1775-1882: Kesaksian Naskah Bo' Bumi Luma Rasanae, Sepuluh Surat Sultan Bima Abdul Hamid Muhammad Syah dan Jawharat al-Ma'arif - Firdausy, Hilmy (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2023)
Not much effort has been made to explore Bima as a historical node within the framework of Islamic epistemology in Nusantara. In fact, the area that was formerly known as the Bima Kingdom became one of the important trading ports that connected the spice shipping routes to the east of the Nusantara. Because of its strategic location and its significance in the connection point of spice shipping in the Nusantara, Bima in the end can not only be read as an economic reality, but also a cultural reality which is a reflection, for example, how religion and politics are dialectic and bargain each other. The book "Iman dan Diplomasi: Serpihan Sejarah Kerajaan Bima" is one that seeks to reveal how this dynamic took place. Through a review of three important scripts, the book describes several important historical facts, not only related to the Bima Kingdom in particular, but also the big agenda of consolidating Islam as a doctrine with factual reality that occurred in the Nusantara from the 18th to 19th centuries.